Zinc as a Neuromodulator in the Central Nervous System with a Focus on the Olfactory Bulb - Blakemore, Laura J.; Trombley, Paul Q. (Frontiers in Cellular Neuroscience, 2017)
The olfactory bulb (OB) is central to the sense of smell, as it is the site of the first synaptic relay involved in the processing of odor information. Odor sensations are first transduced by olfactory sensory neurons before being transmitted, by way of the OB, to higher olfactory centers that mediate olfactory discrimination and perception. Zinc is a common trace element, and it is highly concentrated in the synaptic vesicles of subsets of glutamatergic neurons in some brain regions including the hippocampus and OB. In addition, zinc is contained in the synaptic vesicles of some glycinergic and GABAergic neurons. Thus, zinc released from synaptic vesicles is available to modulate synaptic transmission mediated by excitatory (e.g., NMDA, AMPA) and inhibitory (e.g., GABA, glycine) amino acid receptors. Furthermore, extracellular zinc can alter the excitability of neurons through effects on a variety of voltage-gated ion channels. Consistent with the notion that zinc acts as a regulator of neuronal activity, we and others have shown zinc modulation (inhibition and/or potentiation) of amino acid receptors and voltage-gated ion channels expressed by OB neurons. This review summarizes the locations and release of vesicular zinc in the central nervous system, including in the OB. It also summarizes the effects of zinc on various amino acid receptors and ion channels involved in regulating synaptic transmission and neuronal excitability, with a special emphasis on the actions of zinc as a neuromodulator in the OB. An understanding of how neuroactive substances such as zinc modulate receptors and ion channels expressed by OB neurons will increase our understanding of the roles that synaptic circuits in the OB play in odor information processing and transmission.